2008
DOI: 10.1021/ac085995z
|View full text |Cite
|
Sign up to set email alerts
|

The Realm of the Nanopore

Abstract: The realm of The nanopore Interest in nanoscale research has skyrocketed, and the humble pore has become a king.Jennifer Griffiths little more than 10 years ago, a group of scientists made a discovery that would revolutionize the way DNA was sequenced-or so they hoped. In their 1996 paper (1), the team, which included John Kasianowicz of the U.S. National Institute of Standards and Technology, Daniel Branton of Harvard University, and David Deamer of the University of California Santa Cruz, showed that they co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
38
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 8 publications
2
38
0
Order By: Relevance
“…These values are in good agreement with those found in previous studies of MVCl 2 and Na 2 NDS diffusion through nanoporous membranes. 45,63 In the case of acidic or basic pH, the membrane is charged and the Nernst-Planck equations must be solved using numerical procedures.…”
supporting
confidence: 92%
See 2 more Smart Citations
“…These values are in good agreement with those found in previous studies of MVCl 2 and Na 2 NDS diffusion through nanoporous membranes. 45,63 In the case of acidic or basic pH, the membrane is charged and the Nernst-Planck equations must be solved using numerical procedures.…”
supporting
confidence: 92%
“…7a) gave a surface charge density  = -0.3e nm -2 at pH = 9.5, where e is the elementary charge, and pK C = 4.5. Because at pH = 9.5 all the carboxylate groups are in charged form, it can be concluded that the surface density of groups attached to the pore walls is approximately n C = 0.3 groups/nm 2 . The values of n C and pK C are in agreement with those found in previous studies for the case of pores functionalized with carboxylate groups.…”
Section: 4859-61mentioning
confidence: 99%
See 1 more Smart Citation
“…In nanopore analytics, single molecules are detected via the passage-induced changes in ionic current. [2][3][4][5][6][7] The approach can be implemented with protein 4,[8][9][10] and solid-state nanopores [10][11][12][13][14][15][16] and has gained popularity 17 due to its simplicity, the wide range of accessible analytes, 2,13,[18][19][20] and the prospect of DNA sequencing [21][22][23] based on nucleic acid sensing. [24][25][26][27] The translocation of protein and DNA strands through protein channels is also a biologically relevant process in pathogenic bacteria and human cells.…”
Section: Introductionmentioning
confidence: 99%
“…Biological ion channels located at the cell walls and composed of protein complexes could open and close in response to external stimuli for dominating ion translocation and play crucial role in the creature metabolism process [1]. Inspired by ion channels, researchers have developed various kinds of artificial nanopores or nanochannels to construct biosensors or other devices [2][3][4][5][6][7][8][9][10][11][12][13]. Strictly speaking, under the premise of insuring at least one dimension in the range of one to several dozens of nanometers, pore diameter larger than its depth is simply defined as nanopore while oppositely defined as nanochannel.…”
mentioning
confidence: 99%